Memorizing the words of God: Special reference to ‘Abdul Rahman IBN Khaldun (D. 1406 A.D.) - Bensaid, Benaouda; Machouche, Salah (￼Taylor & Francis Group, 2016)
This study explores the position of the tradition of Qur’an memoriza- tion in the structure of Muslim primary education and intellectual hierarchy while drawing on the Khaldunian perspective regarding the problem of memorization versus comprehension of the Qur’an. This article concludes that the practice of Qur’an memorization is what shapes the spirit and character of Muslim traditional learning, and defines its holistic approach, chain of transmission and author- ity, and moreover characterizes its spiritual collectiveness. Future studies should explore the diverse challenges this tradition encoun- ters today and how they have affected its current course and its contribution toward global Muslim identity.